Assessment of the current agricultural finance sector with major focus on Cocoa: Bank of Ghana (BOG) policy and strategies for financing sustainable agricultural value chains - Dalaa, Mustapha Alasan; Kofituo, Rich Kofi; Annan, Henry; Kortei, Atukwei; Asare, Richard (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
The objective of the assignment was to assess the current agricultural finance sector with a major focus on the cocoa sector and propose measures on how to finance climate smart cocoa production and to develop a blueprint based on the key parameters identified which can be used to formulate a business case for climate smart cocoa financing.